Analysis of Handgrip Strength with Insulin Resistance in Male and Female Indonesian Adults - Kurniawan, Liong Boy; Sheridan, Sabilla; Syafaat, Andi Wali; Surur, Andi Ainun Zulkiah; Nadhifah, Naurah; Afandi, Ichlas Nanang; Ariyandy, Andi; Basri, Muhammad Iqbal; Aminuddin, Aminuddin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Insulin resistance, a precursor to diabetes mellitus and metabolic syndrome, has increased in prevalence in recent decades. Grip strength reflects muscle strength and is thought to provide an overview of the condition of insulin sensitivity. The purpose of this study was to evaluate the association between insulin resistance and handgrip strength in male and female Indonesian adults. This cross-sectional study recruited 169 adult participants, 71 of the subjects were males and 98 of the subjects were females. Handgrip strength, insulin, fasting glucose, HOMA-IR, and OGTT were measured, then the association between handgrip strength and insulin resistance was assessed. Linear regression analysis showed that in male subjects, relative handgrip strength was negatively associated with log HOMA-IR (univariate: B= -0.703, beta= -0.323, p=0.006; multivariate: B= -0.687, beta= -0.316, p=0.012) while no association was found in female subjects (univariate: B= -0.192, beta= -0.136, p=0.183; multivariate: B= -0.172, beta= -0.121, p=0.262). The optimal cut-off value of relative handgrip strength to assess insulin resistance is 0.45 (sensitivity 73.3%, specificity 73.1%) in the male group and 0.34 (sensitivity 68.4%, specificity 61.0%) in the female group. The weaker the handgrip strength in males, the higher the HOMA-IR value. In females, no significant correlation showed between handgrip strength and insulin resistance.